2018
DOI: 10.1051/0004-6361/201832974
|View full text |Cite
|
Sign up to set email alerts
|

The XXL Survey

Abstract: Context. We present the results of a study of the active galactic nucleus (AGN) density in a homogeneous and well-studied sample of 167 bona fide X-ray galaxy clusters (0.1 < z < 0.5) from the XXL Survey, from the cluster core to the outskirts (up to 6r500). The results can provide evidence of the physical mechanisms that drive AGN and galaxy evolution within clusters, testing the efficiency of ram pressure gas stripping and galaxy merging in dense environments. Aims. The XXL cluster sample mostly compri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 101 publications
6
22
0
Order By: Relevance
“…In the left panel of Figure 3, we see that AGN fraction is lower in cluster galaxies than that of field galaxies for each redshift bin. This result agrees with other studies in the literature that look at the environmental dependence of AGNs in clusters and fields (e.g., Lopes et al 2017;Koulouridis et al 2018). We infer that at low redshifts, z ≤ 0.5, relatively more AGNs are found in low density field environment surrounding galaxy clusters compared to the regions closer to the core of the clusters.…”
Section: Dependence On Environmentsupporting
confidence: 93%
See 1 more Smart Citation
“…In the left panel of Figure 3, we see that AGN fraction is lower in cluster galaxies than that of field galaxies for each redshift bin. This result agrees with other studies in the literature that look at the environmental dependence of AGNs in clusters and fields (e.g., Lopes et al 2017;Koulouridis et al 2018). We infer that at low redshifts, z ≤ 0.5, relatively more AGNs are found in low density field environment surrounding galaxy clusters compared to the regions closer to the core of the clusters.…”
Section: Dependence On Environmentsupporting
confidence: 93%
“…Outer regions of clusters and low density fields in the immediate vicinity of the clusters are seen to have higher fraction of AGNs at low redshifts, attributed to more efficient mergers while AGN activity is strongly suppressed in the inner regions of rich clusters (e.g. Koulouridis, & Plionis 2010;Koulouridis et al 2018). We find a significant difference between cluster and field AGN fractions for both the cases, when we divide our clusters based on mass and when we do not, which is clearly indicative of an environmental dependence for these intermediate-mass clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Using optical observations, the local density of galaxies is not the only parameter which defines the environmental properties as it is also important to establish in which location within a, e.g., cluster of galaxies a given source is located. The location of an AGN within the group/cluster of galaxies might have a profound effect on the level of accretion and, consequently, on its nuclear power (see, e.g., Koulouridis et al 2018). For example, by exploring the properties of early-type galaxies in the Virgo cluster, Vattakunnel et al (2010) found a suggestive trend be-tween jet power and location within the cluster.…”
Section: Location Of the Rgs Within The Group/cluster Of Galaxiesmentioning
confidence: 99%
“…Previous studies have shown that AGN in clusters of galaxies are strongly affected by their environment, but in a complicated way. Their ability to accrete was found to depend on both their distance from the cluster centre and the mass of the cluster (Koulouridis et al 2018;Ehlert et al 2015). In more detail, the hot intra-cluster medium (ICM) is probably able to strip or evaporate the cold gas reservoir of galaxies (e.g.…”
Section: Introductionmentioning
confidence: 99%